Persuasive Language in A Tourism Video: A Genre Analysis - Anisah, Anisah (Journal of English Education and Teaching, 2025)
Having a long and painful history and current controversy of sharia law implementation, Aceh is massively rebranding its tourism marketing to attract tourists. As the local government holds the control to rebrand the image of this controversial province, this paper aims to analyze the tourism video genre. This is a qualitative study analyzing a tourism video entitled “The Light of Aceh.” To select the data, purposeful sampling was used. The data was obtained from the official Aceh government Youtube Channel. To collect the data, observation sheet was used. As this video is narrated in a persuasive language, this study adopts Bhatia’s approach of genre analysis focusing solely on three stages of linguistic analysis, namely lexical and grammatical characteristics, pattern of the text, and structural strategies. Also additional information was gained from interviewing a former active member of tourism organization. The results on the linguistic analysis show that the narrative on the video delivers the emotional massages that Aceh has wonderful landscapes, a wonderful story to tell and experience, safe for tourists to visit as people are portrayed as kind, welcoming, and harmonious. Some persuasive suggestions and unique rhetorical question are also evidenced in the results. Whilst the results of the interview uncover that the purpose of the video is to rebrand Aceh tourism to become ‘more Aceh’ and the main target of the video is foreign Muslim tourists.